Hybrid peptides derived from natural antimicrobial peptides, indolicidin and ranalexin, exhibit potent antimicrobial activities against Streptococcus pneumoniae in vitro and in vivo / Hassan Mahmood Kzar Jindal - Hassan Mahmood, Kzar Jindal (2018)
Streptococcus pneumoniae is one of the leading causes of morbidity and mortality in both children and adults. This pathogen is responsible for invasive and noninvasive diseases. Moreover, pneumococcus is the most leading cause of community-acquired pneumonia (CAP), meningitis, and bacteremia worldwide. According to WHO, this bacterial pathogen is responsible for 1.6 million deaths each year. Like other gram-positive bacteria, S. pneumoniae is increasingly difficult to treat due to the inappropriate use of antibiotics. At present, S. pneumoniae has developed resistance to conventional drugs including novel antibiotics such as vancomycin. Therefore, finding a new class of antibacterial agents to overcome this serious issue is a top priority worldwide. One of the promising alternatives to today’s antibiotics is antimicrobial peptides (AMPs). AMPs are produced by almost all living organisms as the first line of defense in their innate immune system against microbial infection. In this study, novel synthetic peptides were designed based on two natural templates indolicidin and ranalexin. Out of thirteen newly designed peptides, five hybrid peptides (RN7-IN10, RN7-IN9, RN7-IN8, RN7-IN7, and RN7-IN6) showed the strongest in vitro antibacterial activity against thirty pneumococcal clinical isolates. These four hybrid peptides also showed broad spectrum antibacterial activity against S. aureus, methicillin-resistant S. aureus (MRSA), and E. coli. Moreover, the killing kinetics of peptides demonstrated that the hybrid peptides were able to eliminate pneumococci within 150 min of treatment which is faster than the standard drugs erythromycin and ceftriaxone. The hybrid peptides produced synergism when combined with each other and with standard antibiotics erythromycin and ceftriaxone. In vitro toxicity assessment revealed that none of the designed peptides displayed and toxic effects against human erythrocytes, WRL-68, and NL-20 cell lines at their MIC levels. In silico molecular docking showed that all five hybrid peptides revealed strong binding affinity toward three pneumococcal virulence factors autolysin, pneumolysin, and iv pneumococcal surface protein A (PspA). Mechanism of action of peptides exhibited that the hybrid peptides kill pneumococci by attacking and damaging the integrity of their cellular membranes. Moreover, DNA binding assay showed that at 62.5 μg/ml all hybrid peptides were able to bind effectively to genomic DNA and to prevent it from migrating through the agarose gel, these results suggesting that hybrid peptides could possess another mechanism of action besides their ability to disrupt the cell membrane. Two hybrid peptides RN7-IN10 and RN7-IN8 were selected to test their in vivo therapeutic efficacy. At 20 mg/kg, the peptides were able to protect 30% and 50% of the mice from lethal systemic infection by resistant pneumococcal strain. The combination of both peptides at 10 mg/kg for each was able to protect 60% of the mice. Interestingly, a combination of RN7-IN8 (20 mg/kg) and ceftriaxone (20 mg/kg) were able to provide 100% protection to mice infected with a virulent strain of S. pneumoniae. Infections caused by antibiotic-resistant S. pneumoniae remain a serious threat to human life. The present study demonstrated that AMPs represent a promising new class of antibacterials either as standalone or in combination with traditional antibiotics.